2014
DOI: 10.2172/1160297
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Hydrogen Release Risk and Behavior Modeling: State-of-the-Art Knowledge Gaps and Research Needs for Refueling Infrastructure Safety.

Abstract: Sandia National Laboratories is a multi-program laboratory managed and operated by Sandia Corporation, a wholly owned subsidiary of Lockheed Martin Corporation, for the U.S. Department of Energy's National Nuclear Security Administration under contract DE-AC04-94AL85000. Approved for public release; further dissemination unlimited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…Using computational fluid dynamics (CFD) tools, it is possible to obtain comprehensive information regarding the flow field. Previous numerical investigations can be classified into three types: (1) modelling studies, (2) influence‐factor investigations, and (3) dispersion behaviour research . For modelling studies, it was confirmed that the slip effects of the nonvapour phase should be considered, as the non‐homogeneous equilibrium model (NHEM) exhibited good agreement with the experimental data .…”
Section: Introductionmentioning
confidence: 92%
“…Using computational fluid dynamics (CFD) tools, it is possible to obtain comprehensive information regarding the flow field. Previous numerical investigations can be classified into three types: (1) modelling studies, (2) influence‐factor investigations, and (3) dispersion behaviour research . For modelling studies, it was confirmed that the slip effects of the nonvapour phase should be considered, as the non‐homogeneous equilibrium model (NHEM) exhibited good agreement with the experimental data .…”
Section: Introductionmentioning
confidence: 92%
“…A one-dimensional model for a liquid hydrogen jet, that includes energy conservation along with the mass and momentum conservation previously described, has been developed [22]. A lack of validation data for this model has prompted the development of an experiment at Sandia National Laboratories (Sandia) [23].…”
Section: Gas Release Dispersion and Accumulationmentioning
confidence: 99%
“…To date, no LH 2 RPT has been observed. Pritchard and Rattigan [6] reported in 2010 that no record of a RPT resulting from a LH 2 spill has been found, and subsequent reports addressing hydrogen safety do not mention RPT [7][8][9][10][11][12][13][14]. The absence of LH 2 RPT can be explained either by (i) the low number of experiments and the stochastic nature of the phenomena or (ii) the fact that the underlying physical mechanisms responsible for LNG RPTs are not present for LH 2 spills on water.…”
Section: Introductionmentioning
confidence: 99%